2013
DOI: 10.2215/cjn.00690112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Dialysis Fluid Buffer on Peritoneal Membrane Function in Children

Abstract: SummaryBackground and objectives Double-chamber peritoneal dialysis fluids exert less toxicity by their neutral pH and reduced glucose degradation product content. The role of the buffer compound (lactate and bicarbonate) has not been defined in humans.Design, setting, participants, & measurements A multicenter randomized controlled trial in 37 children on automated peritoneal dialysis was performed. After a 2-month run-in period with conventional peritoneal dialysis fluids, patients were randomized to neutral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 42 publications
1
14
0
1
Order By: Relevance
“…Previous studies have primarily focused on the effects of B/L‐PDF on HPMC survival, peritoneal fibrosis, and epithelial‐mesenchymal transition . HPMC viability is also reportedly reduced by decreased adenosine 5′‐triphosphate levels and inhibition of mitochondrial activity . Our study revealed that L‐PDF containing a high lactate concentration induces apoptosis in HPMCs, with a concomitant decrease in cell number, suggesting that cell injury from high lactate concentrations is caused by apoptosis rather than cell cycle arrest (Figs and ).…”
Section: Discussionsupporting
confidence: 49%
“…Previous studies have primarily focused on the effects of B/L‐PDF on HPMC survival, peritoneal fibrosis, and epithelial‐mesenchymal transition . HPMC viability is also reportedly reduced by decreased adenosine 5′‐triphosphate levels and inhibition of mitochondrial activity . Our study revealed that L‐PDF containing a high lactate concentration induces apoptosis in HPMCs, with a concomitant decrease in cell number, suggesting that cell injury from high lactate concentrations is caused by apoptosis rather than cell cycle arrest (Figs and ).…”
Section: Discussionsupporting
confidence: 49%
“…Since then, some new clinical data have been reported in the pediatric population. A prospective randomized comparison of low GDP fluids revealed better preservation of UF capacity with bicarbonate versus lactate buffer [ 35 ]. Moreover, prospectively collected data in the IPPN suggests improved longitudinal growth in infants treated with low GDP fluids, potentially due to attenuated local and systemic inflammatory and carbonyl stress.…”
Section: Current Pd Solutionsmentioning
confidence: 99%
“…A recent trial demonstrated lower ultrafiltration rates during the first 6 months of PD with fluids with low glucose degradation product content but better preservation of long term PD function as compared to the acidic PD fluids with high glucose degradation product content [ 6 ]. A randomized trial comparing two neutral pH PD fluids with low glucose degradation product content containing either lactate or bicarbonate buffer over 10 months yielded better preservation of ultrafiltration capacity with the bicarbonate PD fluid [ 7 ].…”
Section: Introductionmentioning
confidence: 99%